2018
DOI: 10.1007/s10578-018-0855-z
|View full text |Cite
|
Sign up to set email alerts
|

Latinx Youth in First Contact with the Justice System: Trauma and Associated Behavioral Health Needs

Abstract: This study examines the prevalence of trauma exposure and its association with psychiatric symptoms, substance use, and sexual activity among First-Time Offending, Court-Involved Non-Incarcerated (FTO-CINI) Latinx youth. Latinx youth (N=181), ages 12-18, were recruited from a family court in the Northeastern region of the United States as part of a longitudinal cohort study of 423 FTO-CINI youth. Baseline data on trauma exposure and symptoms, psychiatric symptoms, substance use (alcohol/marijuana), and sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…Latinx youth involved in the justice system have been shown to endorse high rates of trauma exposure (Hoskins et al, 2019). Trauma exposure has been linked to unmet behavioral health needs (i.e., psychiatric symptoms, substance use, and sexual risk behaviors), and unmet behavioral health needs have been linked to recidivism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Latinx youth involved in the justice system have been shown to endorse high rates of trauma exposure (Hoskins et al, 2019). Trauma exposure has been linked to unmet behavioral health needs (i.e., psychiatric symptoms, substance use, and sexual risk behaviors), and unmet behavioral health needs have been linked to recidivism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Latinx youth being overrepresented at every intercept of the justice system (Winkelman et al, 2017), they have been shown to have unmet behavioral health needs (Hoskins et al, 2019). Trauma has also been shown to be an environmental condition that disproportionately affects Latinx youth (Hinton et al, 2013).…”
Section: Study Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…O trauma pode influenciar de forma negativa o desenvolvimento biopsicossocial da criança (Alberto, 2014;Hoskins, Marshall, Koinis-Mitchell, Galbraith, & Tolou-Shams, 2019;Luthar, Crossman, & Small, 2015), sendo este, associado a doença física e mental na idade adulta (Freeman, 2014;Norman, Byambaa, De, Butchart, Scott, & Vos, 2012). Por tal, a exposição a Eventos Potencialmente Traumáticos (EPT) deve merecer a atenção dos investigadores e ser considerada um problema grave de saúde pública (Finkelhor, Turner, Shattuck, & Hamby, 2013;Lang, & Connell, 2017) que, preocupa não só os profissionais desta área, como também os da educação e justiça (Azevedo, & Maia, 2006), considerando os comportamentos apresentados pelos jovens: externalizantes (e.g., agressividade, impulsividade, baixo autocontrolo) e internalizantes (e. g., ansiedade, depressão, medo) (American Psychiatric Association, 2014;Hoskins et al, 2019;Lang, & Connell, 2018;Pechorro, Oliveira, Gonçalves, & Jesus, 2018;Pechorro, Pontes, DeLisi, Alberto, & Simões, 2018).…”
Section: Introductionunclassified
“…Court-involved, nonincarcerated (CINI) youth—those who are legally involved but living in the community—are also more likely to have psychiatric problems compared with general community adolescent samples; between one-third and one-half of this population has a diagnosable psychiatric condition [6]. In addition, 73% have some form of lifetime trauma exposure [7], and approximately 50% of first-time offending youth endorse lifetime marijuana use [8]. Despite high rates of behavioral health (mental health and substance use) disorders among justice-involved adolescents, only 15% of detained youth receive behavioral health treatment; this number falls to 8% once these youth reenter the community [2].…”
Section: Introductionmentioning
confidence: 99%